Wavelength and frequency of axis-switching phenomenon formed over rectangular and elliptical liquid jets. (October 2019) - Jaberi, A.; Tadjfar, M.
Highlights: Experimental and theoretical study of axis-switching phenomenon established over rectangular and elliptical liquid jets. The previous theoretical model was rewritten by looking at frequency analogous to the previous one for wavelength. The model rewrote the Rayleigh's classical analysis in terms of: influence of shape, aspect ratio, and Weber number. This time, instead of a constant power, a logarithmic function was used to evaluate the coefficients. The results were analyzed from the viewpoint of frequency and wavelength. Abstract: A theoretical and experimental study was performed to investigate the wavelength and frequency of axis-switching oscillations established over rectangular and elliptical liquid jets. Several injectors with aspect ratios ranging from 2 to 6 were manufactured for both rectangular and elliptical shapes. Shadowgraph technique was used for flow visualization and high speed photography was employed to capture the flow physics of the liquid jets. The theoretical model developed by Tadjfar and Jaberi (2019) was rewritten by looking at frequency analogous to the previous one for wavelength. The model rewrote the Rayleigh's classical analysis in terms of three segments identifying the influence of shape, aspect ratio, and Weber number. This model was modified to improve predictive accuracy by adding a correction term in terms of powers of aspect ratio. This time, instead of a constant power, a logarithmic function was used to evaluate the coefficients. The modified model improved the predictive accuracy of Rayleigh's model significantly. The results were analyzed from the viewpoint of frequency and wavelength.